New hydrocarbon stabilisers for dispersion polymerisation in supercritical carbon dioxide - Birkin, Natasha (2012)
This thesis details the synthesis of highly C02-soluble hydrocarbon stabilisers using reversible addition fragmentation chain transfer (RAFT) polymerisation techniques, and their application in the dispersion polymerisation of N-vinyl pyrrolidone (NVP) in supercritical carbon dioxide (scC02). Chapter 1 outlines the key themes explored throughout the thesis. This introductory chapter focuses on the RAFT polymerisation process, the use of scC02 as an alternative solvent for polymerisation, and the process of dispersion polymerisation, including the types of stabilisers employed in such reactions. In Chapter 2, the equipment and characterisation techniques are detailed. The high pressure vessels used extensively throughout the thesis are described, including the high pressure variable volume view cell and the 60 ml clamp-sealed autoclave. Polymer characterisation techniques such as scanning electron microscopy (SEM), nuclear magnetic resonance (NMR) and gel permeation chromatography (OPC) are also considered. Chapter 3 is the first of three research chapters, and investigates the synthesis of hydrocarbon stabilisers composed of the monomers of vinyl acetate (V Ac) and vinyl pivalate (VPi) using xanthate-mediated RAFT polymerisation. The phase behaviour of a range of stabilisers in scC02 is determined through cloud point measurements using a high pressure variable volume view cell. The impact of adjustments to parameters such as polymer composition and molecular weight on CO2-solubility are considered. Chapter 4 details the application of the homopolymers and statistical copolymers of V Ac and VPi synthesised in the previous chapter. The polymers are employed as stabilisers in the dispersion polymerisation of NVP in SCC02. A range of stabilisers are considered and the resulting poly(vinyl pyrrolidone) (PNVP) products compared using NMR and SEM to gauge the effect on particle morphology. Chapter 5 describes the extension of the research to consider the impact of changes to the hydrocarbon stabiliser architecture. A series of block copolymer structures are prepared, and the phase behaviour and stabilising ability of these materials in scC02 is considered. Additionally, modification of the alpha- and omega-end of the RAFT-terminated polymers is considered through use of a different xanthate-based RAFT agent, and modification of the polymer post-polymerisation via radical-induced reduction. Chapter 6 describes the overall conclusions obtained from the work presented in the thesis, and also details possible avenues for further research in this area.